Seismic response of buildings during the May 19, 2011 Simav, Turkey earthquake - Yon, Burak; Sayin, Erkut; Koksal, Teoman S. (Techno-Press, 2013)
On May 19, 2011 an earthquake struck Simav district of Kutahya which located west of Turkey. According to Disaster and Emergency Management Agency (DEMA), magnitude of this earthquake was AIL = 5.7. In this earthquake 2 people lost their lives and considerably damages occurred in the city center and surrounding villages. Damaged structures in the earthquake area did not have adequate earthquake resistance since low quality materials, poor workmanship and improper selection of the structural system. In this study, reasons of damages and failure mechanism of reinforced concrete and masonry buildings were evaluated.
Keywords: Simav earthquake; reinforced concrete buildings; masonry buildings; ground motions